Heritabilities and genetic correlations for birth weight, weaning weight, and yearling weight in polled Hereford cattle - J.B. Glaze; R.R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1994)
Performance data from a Polled Hereford herd selected for feed conversion were used in the calculation of heritabilities and genetic correlations for birth weight (BWT), weaning weight (WWT), and yearling weight (YWT). Direct heritabilities for BWT, WWT, and YWT were .31, .16, and .25, respectively. Corresponding maternal heritabilities for BWT, WWT and YWT were .04, .01, and .18, respectively. With the exception of the correlation between WWT and YWT (.98), the other genetic correlations were low to moderate, ranging from -.27 to .12.
Keywords: Cattlemen& #x27; s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Birth weight; Weaning weight; Yearling weight; Heritabilities; Genetic correlations